Inherited determinants of Crohn's disease and ulcerative colitis phenotypes: a genetic association study. Issue 10014 (9th January 2016) - Cleynen, Isabelle; Boucher, Gabrielle; Jostins, Luke; Schumm, L Philip; Zeissig, Sebastian; Ahmad, Tariq; Andersen, Vibeke; Andrews, Jane M; Annese, Vito; Brand, Stephan; Brant, Steven R; Cho, Judy H; et al.
Summary: Background: Crohn's disease and ulcerative colitis are the two major forms of inflammatory bowel disease; treatment strategies have historically been determined by this binary categorisation. Genetic studies have identified 163 susceptibility loci for inflammatory bowel disease, mostly shared between Crohn's disease and ulcerative colitis. We undertook the largest genotype association study, to date, in widely used clinical subphenotypes of inflammatory bowel disease with the goal of further understanding the biological relations between diseases. Methods: This study included patients from 49 centres in 16 countries in Europe, North America, and Australasia. We applied the Montreal classification system of inflammatory bowel disease subphenotypes to 34 819 patients (19 713 with Crohn's disease, 14 683 with ulcerative colitis) genotyped on the Immunochip array. We tested for genotype–phenotype associations across 156 154 genetic variants. We generated genetic risk scores by combining information from all known inflammatory bowel disease associations to summarise the total load of genetic risk for a particular phenotype. We used these risk scores to test the hypothesis that colonic Crohn's disease, ileal Crohn's disease, and ulcerative colitis are all genetically distinct from each other, and to attempt to identify patients with a mismatch between clinical diagnosis and genetic risk profile. Findings: After quality control, the primary analysis included 29 838 patients (16 902 with Crohn's disease, 12 597 with ulcerative colitis). Three loci ( NOD2, MHC, and MST1 3p21) were associated with subphenotypes of inflammatory bowel disease, mainly disease location (essentially fixed over time; median follow-up of 10·5 years). Little or no genetic association with disease behaviour (which changed dramatically over time) remained after conditioning on disease location and age at onset. The genetic risk score representing all known risk alleles for inflammatory bowel disease showed strong association with disease subphenotype (p=1·65 × 10 −78 ), even after exclusion of NOD2, MHC, and 3p21 (p=9·23 × 10 −18 ). Predictive models based on the genetic risk score strongly distinguished colonic from ileal Crohn's disease. Our genetic risk score could also identify a small number of patients with discrepant genetic risk profiles who were significantly more likely to have a revised diagnosis after follow-up (p=6·8 × 10 −4 ). Interpretation: Our data support a continuum of disorders within inflammatory bowel disease, much better explained by three groups (ileal Crohn's disease, colonic Crohn's disease, and ulcerative colitis) than by Crohn's disease and ulcerative colitis as currently defined. Disease location is an intrinsic aspect of a patient's disease, in part genetically determined, and the major driver to changes in disease behaviour over time. Funding: International Inflammatory Bowel Disease Genetics Consortium members funding sources (see Acknowledgments for full list).